Performance analysis of dye sensitized solar cell based on ZnO compact layer and TiO2 photoanode - Rahman, Abdur; Mahmud, Md. Ashik; Haque, Md. Injamamul (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.